Opini Masyarakat Desa Kertosari Jember Seputar Perubahan Tempat Pengolahan Akhir Sampah (TPA) Menjadi Objek Wisata Edukatif - Swandayani, Ana; Juariyah, Juariyah (Universitas Muhammadiyah Jember, 2019)
This study aims to describe the Opinion of the Village Community of Kertosari Jember Regarding Changes in the Final Waste Management Site (TPA) into Educational Tourism Objects by using a type of qualitative research through a descriptive approach obtained from primary and secondary data through observation, interviews and documentation using the data analysis model Miles and Huberman with steps Data Collection, Data Reduction, Data Presentation, and Data Verificationdone in a way to get the actual data.In this study it was found that public opinion and visitors were positive and negative. The positive thing is that some of them agree with the TPA change to become a tourist attraction because it has benefits for the surrounding community and visitors who come for example as a place to take pictures,educational sites such as learning waste processing, recycling waste, making compost, and making methane gas. The negative thing about odors that interfere with breathing causes the health of the community to be disturbed, especially young children, and polluted river water due to the presence of rubbish deposits. From this it can be concluded that the surrounding community was disturbed by the pungent odorin the village and the water that becomes cloudy, this can be overcome by communication between the landfill manager and the surrounding community so that the community feels comfortable with the TPA in the village.Keywords: Community Opinion, Waste Final Processing Site (TPA), Educational Tourism.